Effects of formulation on the stability of green Cyclopia subternata extract during spray-drying and storage - Pauck, Claire Elizabeth (Stellenbosch : Stellenbosch University, 2016)
Thesis (MSc Food Sc)--Stellenbosch University, 2016.